2020
DOI: 10.1103/physrevresearch.2.033462
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic mixed valent semimetal EuZnSb2 with Dirac states in the band structure

Abstract: We report discovery of antiferromagnetic semimetal EuZnSb 2 , obtained and studied in the form of single crystals. Electric resistivity, magnetic susceptibility, and heat capacity indicate antiferromagnetic order of Eu with T N = 20 K. The effective moment of Eu 2+ inferred from the magnetization and specific heat measurement is 3.5 μ B , smaller than the theoretical value of Eu 2+ due to presence of both Eu 3+ and Eu 2+. Magnetic-fielddependent resistivity measurements suggest dominant quasi-two-dimensional F… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 66 publications
(74 reference statements)
1
4
0
Order By: Relevance
“…Free refinement of the occupancies with constrained atomic displacement parameters revealed that whenever the Zn1 site is occupied, it is tetrahedrally coordinated by two Sb5 atoms, showing full occupation and located at a distance of 2.79 Å from Zn1, and two Sb3B sites, located at a distance of 2.75 Å (Table ). These values are in good agreement with bonding Zn–Sb contacts in other structures hosting ZnSb 4 tetrahedra. ,, …”
Section: Resultssupporting
confidence: 84%
“…Free refinement of the occupancies with constrained atomic displacement parameters revealed that whenever the Zn1 site is occupied, it is tetrahedrally coordinated by two Sb5 atoms, showing full occupation and located at a distance of 2.79 Å from Zn1, and two Sb3B sites, located at a distance of 2.75 Å (Table ). These values are in good agreement with bonding Zn–Sb contacts in other structures hosting ZnSb 4 tetrahedra. ,, …”
Section: Resultssupporting
confidence: 84%
“…The MR( H ) data show a crossover from the low‐field H 2 dependence to the high‐field unsaturated linear dependence behavior, usually observed in Dirac materials. [ 45–47 ] Because all massless Dirac fermions occupy the lowest Landau level in the quantum limit, the bands with Dirac linear energy dispersion would lead to a giant non‐saturating linear magnetoresistance, [ 48 ] which is supported by our first‐principles calculations in Figure 2. To characterize the crossover behavior from low‐field H 2 dependence to high‐field linear dependence, the field derivative of MR( H ) is presented in Figure 5(c).…”
Section: Resultsmentioning
confidence: 52%
“…As earlier indicated EuZnSb 2 is also a TDSM, 207 and along with other related phases 212–215 presents a fruitful playground to explore the influence of a complex band structure and Dirac bands to achieving excellent TE performance. It, therefore, remains to be seen how the robust electronic band structure of the various phases will play out as it pertains to the evolution of their respective TE transport properties.…”
Section: Intuitions Developed From Some Known and Newly Discovered Zi...mentioning
confidence: 91%
“…The Zintl phases YbMnSb 2 206 and EuZnSb 2 207 are topological Dirac semimetals (TDSM), which similarly to TIs have in their bulk band structures an inverted order of the occupied valence and unoccupied conduction bands at the time-reversal invariant momenta (TRIM) in the Brillouin zone (BZ). However, as opposed to TIs ( vide supra ), the band inversion in TDSMs is characterized by a two-dimensional topological invariant, ν 2D = 1 which results in the appearance of Dirac cones already in the bulk and which is protected by crystalline symmetries.…”
Section: Intuitions Developed From Some Known and Newly Discovered Zi...mentioning
confidence: 99%